Signaling Cooperation - Matthias Heinz; Heiner Schumacher (ZBW - Deutsche Zentralbibliothek für Wirtschaftswissenschaften, Leibniz-Informationszentrum Wirtschaft, 2016)
We examine what an applicant's vita signals to potential employers about her willingness to cooperate in teams. Intensive social engagement may credibly reveal that an applicant cares about the well-being of others and therefore is less likely to free-ride in teamwork situations. We find that contributions in a public goods game strongly increase in a subject's degree of social engagement as indicated on her résumé (and rated by an independent third party). Engagement in other domains, such as student or sports associations, is not positively correlated with contributions. In a prediction experiment with human resource managers from various industries, we find that managers use résumé content effectively to predict relative differences in subjects' willingness to cooperate. Thus, young professionals signal important behavioral characteristics to potential employers through the choice of their extracurricular activities.
Keywords: C72; C92; D82; 330